PWE-091 L-ornithine L-aspartate in minimal hepatic encephalopathy: possible effects on the brain-muscle axis?. (8th June 2018) - Pasha, Y; Taylor-Robinson, S; Leech, R; Ribeiro, I; Cook, N; Crossey, M; Marcinkowski, H
Abstract : Introduction: L-Ornithine L-Aspartate (LOLA) is an ammonia-lowering agent for treatment of hepatic encephalopathy (HE); it may reduce sarcopenia. We investigated 12 weeks of oral LOLA in patients with compensated cirrhosis and minimal HE (MHE). Methods: Consecutive patients were pre-screened with paper-and-pencil-based psychometric testing (PHES test) and included if performance was impaired to a level of −4 or worse. 34 English-speakers were included; 12 randomised to 12 weeks oral LOLA 6 g tds, 22 randomised to identical-looking placebo. At baseline, 4 and 12 weeks, subjects had PHES, a computerised battery: Cogstate TM and SF-36 health questionnaires. Markers of muscle function were recorded: handgrip strength, skin fold thickness, and 6-minute-walk-test. Subjects had cerebral T1 and T2 MRI, functional MRI (fMRI) with motor/cognitive tasks/resting state studies; and 1 H MRS. LC Model software was used for metabolite identification. Results: On SF-36, 57% on LOLA reported better energy levels than placebo 0.04% (P-value<0.001). Better concentration was reported by 21% in treatment arm vs none in placebo group (p=0.05). 28% reported improved memory in treatment group vs 0.04% with placebo. Sleep improvements were reported by 35% in treatment arm vs 0.09% on placebo (p=0.05). In both groups, changes in total PHES score and Cogstate TM were non-significant. PHES test sub-analysis of the Digit-Symbol showed significant improvement in performance in LOLA-treated group (p=0.05). Biceps skinfold thickness showed a mean gain of 1.5 mm in the LOLA group with mean loss of 1.0 mm (p=0.05) in placebo. No differences were found in other skinfolds, hand-grip or 6-minute-walk-test. On T1 cerebral MRI, significant volume reduction was seen in left lateral ventricle, right globus pallidus and mid-anterior corpus callosum (ACC). fMRI tasks did not vary between groups. 1 H MRS of ACC showed significant changes in glutamate concentration (p=0.03), after LOLA. Conclusion: After 12 weeks LOLA, patients reported highly significant improvement in energy levels and concentration. Although 12 weeks LOLA had no overall effect on psychometric performance, significant treatment-related improvement in digit-symbol PHES subtest in those receiving LOLA was seen. An increase was noted in biceps skinfold thickness, which may indicate improved nutrition. Subcortical brain areas showed volume reduction, an observation not previously noted in imaging studies of patients receiving this drug. Unlike previous studies, no functional changes were seen, but significant changes were found on MRS of ACC, a region known to be metabolically active in mHE. It may be that a larger dose of LOLA would have shown greater effects on psychometric performance.